PENDAMPINGAN SERTIFIKASI HALAL PADA UMKM PRODUK MINUMAN SEHAT RORESE KHAS SERDANG KULON TANGERANG - Rachman, Abdul; Muizzudin; Bishri, Mochammad Hasan; Muthi'ahfatin, Nabilah; Henrieka, Yasmin Nabila; Puryani, Suci; Hajar, Ibnu; Septiawan, Fery; Setiyati, Siti Nur; Berlina; Amelia, Virna; Julianti, Niken; Maulida, Mesya Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Based on Law Number 33 of 2014 concerning Halal Product Guarantees, BPJPH is the institution that has the authority to carry out Halal Certification in Indonesia. Halal Certification is an acknowledgment of the halalness of a product. One of the programs offered by BPJPH is Free Halal Certification (Self Declare) for MSMEs in Indonesia. This service aims to provide assistance with Free Halal Certification (Self Declare) for MSME players of the Rorese (Rosella Flower) healthy drink product typical of Serdang Kulon Village, Panongan District, Tangerang Regency. Halal Certification assistance is carried out to provide halal certainty for Rorese's healthy drink products and improve product quality and added value to Rorese's healthy drink products. Products that have been certified halal are one of the marketing strategies to increase sales in the global market, not just locally. This service method uses the PAR (Participatory Action Research) method, which is a method that involves many parties related to assisting Halal Certification for MSMEs in Rorese healthy drink products, Serdang Kulon Village, Panongan District, Tangerang Regency. Assistance with Halal Certification for MSMEs of Rorese healthy drink products is carried out by first creating a NIB (business identification number) with KBLI 11040 Soft Drink Industry, then continuing with registering Rorese healthy drink products on the SiHalal website-based application https://ptsp.halal.go. id/login. In the registration process on the SiHalal application, what is done in the service is preparing a business actor profile, product photos with complete packaging, filling in the SJPH, several raw materials used, production processes, and so on. This dedication produces Rorese healthy drink products which are certified halal by BPJPH and have an NIB (business identification number) so that MSMEs who produce Rorese healthy drink products typical of Serdang Kulon Village can be assured of their halal status and improve product quality and added value to Rorese healthy drink products so that they can be made wrong. a marketing strategy to increase sales in the global market both offline and online. Abstrak Berdasarkan UU Nomor 33 tahun 2014 tentang Jaminan Produk Halal, BPJPH merupakan lembaga yang berwenang menyelenggarakan Sertifikasi Halal di Indonesia. Sertifikasi Halal merupakan pengakuan kehalalan suatu produk. Salah satu program yang ditawarkan oleh BPJPH adalah Sertifikasi Halal Gratis (Self Declare) untuk pelaku UMKM di Indonesia. Pengabdian ini bertujuan melakukan pendampingan Sertifikasi Halal Gratis (Self Declare) bagi pelaku UMKM produk minuman sehat Rorese (Bunga Rosela) khas Desa Serdang Kulon, Kecamatan Panongan Kabupaten Tangerang. Pendampingan Sertifikasi Halal dilakukan untuk memberikan kepastian kehalalan pada produk minuman sehat Rorese dan meningkatkan kualitas produk dan nilai tambah (add value) pada produk minuman sehat Rorese. Produk yang telah tersertifikasi halal menjadi salah satu strategi marketing untuk dapat meningkatkan penjualan pada pasar global bukan saja lokal. Metode pengabdian ini menggunakan metode PAR (Participatory Action Research), yaitu metode yang melibatkan banyak pihak yang berkaitan dengan pendampingan Sertifikasi Halal pada pelaku UMKM produk minuman sehat Rorese Desa Serdang Kulon, Kecamatan Panongan Kabupaten Tangerang. Pendampingan Sertifikasi Halal pada pelaku UMKM produk minuman sehat Rorese dilakukan dengan pembuatan NIB (nomor induk berusaha) terlebih dahulu dengan KBLI 11040 Industri Minuman Ringan kemudian dilanjutkan dengan mendaftarkan produk minuman sehat Rorese pada aplikasi berbasis website SiHalal https://ptsp.halal.go.id/login. Dalam proses pendaftaran pada aplikasi SiHalal, yang dilakukan dalam pengabdian adalah menyiapkan profile pelaku usaha, foto produk dengan kemasan lengkap, pengisian SJPH, beberapa bahan baku yang digunakan, proses produksi, dan lain sebagainya. Pengabdian ini menghasilkan produk minuman sehat Rorese yang tersertifikasi halal oleh BPJPH dan memiliki NIB (nomor induk berusaha) sehingga pelaku UMKM produk minuman sehat Rorese khas Desa Serdang Kulon dapat dipastikan kehalalannya dan meningkatkan kualitas produk dan nilai tambah pada produk minuman sehat Rorese sehingga dapat menjadi salah satu strategi marketing dalam meningkatkan penjualan pada pasar global baik secara offline maupun online.